13x -2(3x -4) = 6(x +2) -4 =

13x -6x +8 = 6x +12 -4 =

7x +8 = 6x +8 =

7x +8 -8 = 6x +8 -8 =

7x - 6x = 6x -6x =x

x or 0 ?

Results 1 to 3 of 3

- Jan 27th 2009, 06:14 PM #1

- Joined
- Jan 2009
- From
- in space
- Posts
- 60

- Jan 27th 2009, 06:17 PM #2

- Joined
- Dec 2008
- From
- Scotland
- Posts
- 901

x = 0 is the solution to the equation.

You can see this by plugging it into the original equation:

$\displaystyle 13x - 2(3x-4) = 6(x+2)-4 $

$\displaystyle 13(0) - 2(3(0)-4) = 6(0+2)-4 $

$\displaystyle - 2(-4) = 6(2)-4 $

$\displaystyle 8 = 12-4 $

$\displaystyle 8 = 8 $

Yey.

- Jan 27th 2009, 06:42 PM #3

- Joined
- Jan 2009
- From
- in space
- Posts
- 60